2021
DOI: 10.3390/pediatric13020037
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Breastfeeding in 2021 and Beyond—Lessons from the Pandemic

Abstract: The COVID-19 pandemic has affected maternal and infant health globally both directly from infection with the SARS-CoV-2 virus and indirectly from changes in health care resulting from social, economic, and health care policies unique to each country. The developing countries have to share the disproportionate burden on maternal and infant health. In this review, we discuss the uncertainties resulting from SARS-CoV-2 infection in pregnancy, vertical transmission of the virus, and its effects on breastfeeding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 69 publications
1
14
0
12
Order By: Relevance
“…However, the same authors have shown how the structures committed to the UNICEF Baby-Friendly Hospital Initiative (BFHI) managed to guarantee standards of care and procedures similar to those before the pandemic and provided better support for mothers with and without COVID-19. In addition to ongoing and unchanged support from health professionals, some authors have suggested new ways to ensure adequate help for nursing mothers during a pandemic [27, 28]. Telemedicine has been adopted to improve support for pregnant women in managing peculiar situations, such as gestational diabetes or weight gain [29].…”
Section: Possible Strategies For Breastfeeding Protection and Promotionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the same authors have shown how the structures committed to the UNICEF Baby-Friendly Hospital Initiative (BFHI) managed to guarantee standards of care and procedures similar to those before the pandemic and provided better support for mothers with and without COVID-19. In addition to ongoing and unchanged support from health professionals, some authors have suggested new ways to ensure adequate help for nursing mothers during a pandemic [27, 28]. Telemedicine has been adopted to improve support for pregnant women in managing peculiar situations, such as gestational diabetes or weight gain [29].…”
Section: Possible Strategies For Breastfeeding Protection and Promotionmentioning
confidence: 99%
“…Adequate prenatal training on breastfeeding can also be successfully conducted electronically [31]. A review by Singh et al [27] has summarized some of these innovative strategies, which are able to reach mothers even in rural or particular contexts and which appear to be an up-and-coming tool for the promotion and protection of breastfeeding in times of pandemic.…”
Section: Possible Strategies For Breastfeeding Protection and Promotionmentioning
confidence: 99%
“…Once at home, breastfeeding women experienced reduced access to lactation and mental health support [4 ▪ ,5,6]. The combination of restrictive policies, misinformation, and lack of evidence complicated the provision of human milk (HM) and maternal-infant bonding during the early months of the pandemic [7 ▪▪ ].…”
Section: Coronavirus Disease 2019 Policies For Pregnant and Breastfee...mentioning
confidence: 99%
“…Several strategies have been proposed to help women across different stages in pregnancy and lactation during the pandemic (Table 1) [7 ▪▪ ]. Lactation telehealth services, including digital applications, telephone, mobile phone, and video conferencing, have been demonstrated to be equally effective and feasible in higher and lower-income populations.…”
Section: Perinatal Support Moving Forward In the Pandemicmentioning
confidence: 99%
“…While in-person pediatric consultations are invaluable, telehealth changes how care and education can be delivered. One such positive example is the role of telehealth in promoting breastfeeding [ 18 ]. In our opinion, telehealth, if accessible to all parents, provides an opportunity to promote appropriate infant feeding practices, and it is likely to help in improving the health and development of children.…”
Section: Discussionmentioning
confidence: 99%